Spring Boot in practice - Musib, Somnath (Manning Publications, 2022)
Go beyond the basics with Spring Boot! This practical guide presents dozens of relevant scenarios in a convenient problem-solution-discussion format. In Spring Boot in Practice you will learn: Spring Boot's features from an expert's perspective Configuring, logging, and monitoring Spring Boot applications Effective methods for database communication Utilizing Spring Security and securing your Spring application in production Designing and developing microservices and RESTful APIs with Spring Boot Microservice versioning, documentation, and security Reactive application development and reactive data access with WebSocket and RSocket Deploying Spring Boot applications on Kubernetes and major cloud platforms Implementing containerization in a Spring Boot application Using Spring Boot with Kotlin and GraalVM Spring Boot in Practice is full of practical recipes for common development problems in Spring Boot. Author Somnath Musib has spent years building applications with Spring, and he shares that extensive experience in this focused guide. You'll master techniques for using Spring Data, Spring Security, and other Spring-centric solutions. Learn how to work with Spring Boot and Kotlin, handling connections for multiple platforms, and how Spring Boot can simplify building microservices and APIs. Each recipe is built around a real-world problem, complete with a full solution and thoughtful discussion. About the Technology With Spring Boot, it's a snap to create standalone Spring applications that require minimal manual setup. Spring Boot directly embeds a server like Tomcat or Jetty into your project and preconfigures core Spring settings, third-party libraries, security, and other key elements. It's a big framework, with lots of powerful features. This book provides a rich collection of techniques to help you get the most out of Spring Boot. About the Book Spring Boot in Practice is a cookbook-style guide to Spring application development. Following a convenient Problem-Solution-Discussion format, it takes you technique-by-technique through Spring Boot fundamentals. You'll dive deep into auto-configuration, security, microservices, and more. Along the way, you'll also discover numerous advanced and hidden features. All the book's source code is open source, so you can integrate the detailed samples into your own projects. What's Inside Instantly useful techniques with reusable source code Configuring, logging, and monitoring Spring Boot applications Effective methods for database communication Securing Spring applications in production Microservices and RESTful APIs About the Reader For Spring Boot beginners with some Spring experience. About the Author Somnath Musib has over a decade of development experience, and has been actively working with Spring Boot since 2015. Quotes Your reliable guide to Spring...Somnath Musib does a great job, and his expert guidance makes it easy to focus on the journey that matters: the journey to production. - Josh Long, Spring Developer Advocate, Tanzu, a division of VMWare A-Z guide for Spring Boot. - Najeeb Arif, Thoughtworks Hands-on recipes and best practices that help you build applications faster. - Joô Miguel Pires Dias, Mercedes-Benz.io Invaluable for creating robust API frameworks rapidly and leveraging microservice best practices. - Lachman Dhalliwal, Netcompany.
Online resource; title from title details screen (O'Reilly, viewed October 25, 2023)
Keywords: Spring Boot (Electronic resource); Application software -- Development; Logiciels d'application; Développement; Application software; Development; Audiobooks; Livres audio